Synthesis and Characterization Two Nanocomposites of Fe3O4 Nnanoparticles and Using Them as a Chemical Sensors - Abdul Raheem Nemea, Ameer; I. Al-Abdaly , Basim (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
The sensor aspect is one of the most critical disciplines due to its wide application in life. This work has studied the performance of the Fe3O4 nanocomposite, which was prepared by the synthesis of Fe3O4 nanoparticles (NPs) by the co-precipitation method through its precursors, which are ferric chloride and ferrous chloride. On the other hand, graphene oxide was synthesized using the Hummers method. Chemical sensing is a process that converts a chemical or physical change of a specific analyte into a measurable signal whose magnitude is usually proportional to the concentration of the analyte. The chemical sensor is an analyzer that responds to a particular analyte and reflects that response into an analytical electrical signal. The carbon nanotubes (CNTs) have been purchased to provide two matrixes (substrates) for nanocomposites. The sonication technique has been used to prepare the composites: the first nanocomposite is made of iron oxide NPs and graphene oxide NPs, and the second is made of iron oxide NPs with CNTs. Many techniques, such as AFM, SEM-EDX, FTIR, and XRD, have been used for characterization. There are specific factors indicated in the sensing, which are sensitivity, response time, and recovery time. In the Fe3O4/CNT nanocomposite state, the sensitivity is higher than that of Fe3O4/GO, and there is also a difference between them in response and recovery times. It has been observed that there was a difference between the two nanocomposites in the pattern of the cyclic voltammetry curve, with Fe3O4/CNTs being more regular than Fe3O4/GO for sensing glucose molecules.